Discussion on Dynamic Self-Adapting Management for Future Network - Wenjing Li (Dianxin kexue)
The new requirements for network management introduced by future network and virtual network environment were described.The network management mode under the network virtualization environment was discussed,and it was clarified that the dynamic self-adapting management was the direction of the future network management.Three research aspects of dynamic self-adapting management were proposed:information perception,resource management and across-network negotiation,and the research contents were analyzed.